LIBERAL ECONOMIC ORDER AND ITS COUNTERFACTUAL ASPECTS (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2020)
I criticize the definition Eros GRAU (2017) offers to the liberal economic order. I start from the author's own assumptions and, based on the revised bibliography, I propose alternative answers to the problems that remained opened after that criticism. I conclude the author's mistakes consist of: conceiving that order as a period in the regulatory history of the capitalist economy; conceiving that, under that order, the role of the State and of the Law were limited to portraying the preview existing economic reality. Alternatively, I conclude that order should be conceived, as well as the interventionist economic order, just as models for understanding the legal regulation of capitalism, in which both orders always coexisted, although eventually one prevails over the other; and I conclude that order was not a portrayed reality, but an ideal of reality, conceived by the natural law philosophy and expressed by the first economists; an ideal that never really corresponded the existing capitalism. I hope this paper helps to overcome ideas that oblique the role of Law and of the State in shaping the economy. So contrary to the ideological defense of the liberal economic order, I conclude it is no less counterfactual than interventionist order. Keywords: Economic order; liberalism; economic interventionism.